The Role of Renewable Energy Use in Making Company Operational Costs Efficiency: A Case Study of PT Chandra Asri Petrochemical Tbk - Evracia Turukay; Muhammad Dzakwan Dzaky; Nur Ain Yahya; Michelle Patty (Pattimura Proceeding, 2026)
The transition from dirty energy to renewable energy is a crucial solution to address the problem of carbon dioxide (CO₂) emissions that impact the global climate, particularly for manufacturing industries in Indonesia such as PT Chandra Asri. This study aims to analyze the effect of renewable energy implementation on the company's operational costs during the 2014-2024 decade. The method used is a qualitative approach with secondary data analysis from PT Chandra Asri's financial statements and sustainability reports. The results show that although the initial investment in renewable energy is relatively high, the company's operational costs have decreased significantly over time. Analysis using the Operating Expense Ratio (OER) and Return on Investment (ROI) shows that the OER fluctuates, but shows a downward trend after the implementation of renewable energy. Meanwhile, ROI increases rapidly within two years after the initial investment, indicating potential long-term benefits. This study concludes that the transition to renewable energy not only contributes to reducing carbon emissions but also optimizes the company's operational costs. Thus, the implementation of renewable energy is a strategic step that provides economic benefits and environmental sustainability for PT Chandra Asri.